Program latihan dan pengurusan kewangan pasukan pancaragam Sekolah Menengah Kebangsaan Victoria, Kuala Lumpur: satu kajian kes (IR) - Hishammuddin Idrus (2009)
The Victoria Institution Cadet Corps Band (VICCB) has acclaimed successes at national and international level. These national and international triumphs have certainly proven that VICCB has the right factors in preserving its name as an outstanding, prestigious and victorious band in Malaysia. This research focuses on two aspects; firstly, on the training program carried out by VICCB which includes its organisation, the training program for its new recruits and the role of its band director in dealing with the band, secondly, this research is aimed at determining the type of expenses and steps taken to attain financial sources in order to provide for the band activities. This research is done in a qualitative approach. The method used is a case study. The data is collected through interviews. The findings of the research have clearly indicated that the successes gained by VICCB are due to its competent organisational structure, the systematic training program and strong financial sources.